E-016 An Atherosclerotic Plaque Phantom for Medical Imaging. (29th July 2016) - Chueh, J; Turan, T; van der Marel, K; LeMatty, T; Brown, T; Ansari, S; Carroll, T; Buck, A; Zhou, X; Chatterjee, A; King, R; Zheng, S; et al.
Abstract : Introduction: Intracranial atherosclerotic disease (ICAD) is a common cause of ischemic stroke, but little is known about how the characteristics of intracranial plaques are related to stroke risk. Recently, studies have attempted to correlate ICAD lesions with high-resolution MRI (HR MRI) vessel wall findings, an important emerging technology, to identify various plaque components. However, long-term, multi-center clinical studies are needed to show if HR MRI plaque components contribute to stroke risk. The goal of this study is to build an ICAD phantom that incorporates materials mimicking a stenotic vessel and plaque components (fibrous cap and lipid core) for standardizing MRI pulse sequences across multiple imaging platforms necessary for development of multi-center ICAD HR MRI networks. Materials and methods: HRMRI data from a patient with a basilar artery plaque was used to acquire the detailed structure of the stenotic artery and plaque components. A virtual core-shell mold of the basilar artery plaque was 3D printed to form a physical object. During 3D printing, the volume and shape of each plaque component were defined in the model. Polyvinyl alcohol hydrogel was infused into the core-shell mold to form the stenotic artery. A fibrous cap was constructed using a mixture of agarose, carrageenan, sodium azide, and water. The lipid core was mimicked using vegetable fat, sodium azide, and carrageenan mixture. Two phantoms were manufactured and scanned using various 3 T MRI systems across 7 different sites for image quality assessment. Quantitative comparisons of the scan results for both structural dimensions of plaque components (e.g. lumen diameter) and contrast-to-noise ratio (CNR) were based on the thin cross-sectional slices from 3D T2-weighted TSE/FSE sequences. Results: HRMRI provides a detailed benchmark for validation of lumen geometry (Figure 1A, top). Quantitative evaluation of the lumen diameter in the vicinity of the stenosis using imaging data acquired from 7 different centers is presented as weighted mean and standard deviation (Figure 1A, bottom). It was observed that along the centerline of the lumen, the radius ranged from 0.8–1.6 mm and was highly reproducible across all imaging platforms. The highest CNRs were observed for comparisons between lipid and vessel wall (Figure 1B ). CNR mean variation between the two phantom models for each comparison between plaque components was 3.68–6.09, demonstrating excellent reliability in manufacturing technique. Conclusion: A plaque phantom composed of a stenotic vessel wall and plaque components, including fibrous cap and a lipid core, was successfully constructed for multi-center HRMRI standardization. Disclosures: J. Chueh: None. T. Turan: None. K. van der Marel: None. T. LeMatty: None. T. Brown: None. S. Ansari: None. T. Carroll: None. A. Buck: None. X. Zhou: None. A. Chatterjee: None. R. King: None. S. Zheng: None. R. Swartz: None. E. Feldmann: None. M. Gounis: None.